2019
DOI: 10.3389/fpsyg.2019.01671
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Successful Marathon Runners? The Role of Sex, Age, Education, and Training Experience in Polish Runners

Abstract: The aim of this study was to compare the motivations of successful marathon finishers ( n = 1,243) and inexperienced runners (control group, n = 296). A total of 1,537 runners with 380 women (24.7%) and 1,157 men (75.3%) completed the motivations of marathoners scales (MOMS) questionnaire and the relationships between general motivation categories and selected demographic (e.g., gender, age, and education) and training characteristics were analyzed. Successful mara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 43 publications
4
79
0
4
Order By: Relevance
“…The aim of this research was to describe why athletes decide to take part in a marathon, i.e., runners’ reasons for participation, focusing on some characteristics of participants, such as their age, sex, and marital status, with some of these variables being previously analyzed in other endurance races ( Nikolaidis et al, 2019 ; Waśkiewicz et al, 2019b ) and in other social contexts ( Buning and Walker, 2016 ; Malchrowicz-Mośko et al, 2019 ; Parra-Camacho et al, 2019 ). The main findings showed that some of the variables analyzed, namely, sex and age, influence the reasons for participation by amateur athletes, while marital status did not evidence any such association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this research was to describe why athletes decide to take part in a marathon, i.e., runners’ reasons for participation, focusing on some characteristics of participants, such as their age, sex, and marital status, with some of these variables being previously analyzed in other endurance races ( Nikolaidis et al, 2019 ; Waśkiewicz et al, 2019b ) and in other social contexts ( Buning and Walker, 2016 ; Malchrowicz-Mośko et al, 2019 ; Parra-Camacho et al, 2019 ). The main findings showed that some of the variables analyzed, namely, sex and age, influence the reasons for participation by amateur athletes, while marital status did not evidence any such association.…”
Section: Discussionmentioning
confidence: 99%
“…This constitutes an attempt to describe whether the reasons for a person taking part in an endurance event depend on athletes’ sex and age. Other variables such as years’ experience running ( Ogles and Masters, 2003 ; Malchrowicz-Mośko et al, 2020 ) or training experience ( Waśkiewicz et al, 2019b ) and athletes’ performance ( Ferrer et al, 2015 ; Nikolaidis et al, 2019 ) have also been associated with athletes’ motivations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For marathoners, for example, elite marathoners from Kenya [44] and Ethiopia [45] run for money to support their families. In contrast, marathon runners from Poland [46] and Greece [47] were not running to earn money.…”
Section: The Aspect Of Nationalitymentioning
confidence: 94%
“…For example, motivation differs between female and male marathon runners [22]. It has been shown that female marathon finishers exceeded men on the motivational scales for body weight concern, affiliation, psychological coping, life meaning, and self-esteem, and they scored lower on competitive motivation [23]. Future studies might investigate the motivation of female and male tower runners by age group and performance level.…”
Section: Sex Difference In Performancementioning
confidence: 99%